Improving the perception of Christmas Island Frigatebirds by local fishermen on Pulau Untung Jawa, Jakarta, using the Penyuluhan method - Agung Sedayu; Ani Mariani; Mieke Miarsyah (KUKILA, 2020)
Human-wildlife conflict is a major threat to many declining wildlife species worldwide. The roosting population of the endangered Christmas Island Frigatebird at Pulau Rambut, Teluk Jakarta, is prone to entanglement in fishing lines and nets used by local fishermen for catching fish. We conducted interviews with local fishermen during May-July 2018 in order to quantify their perception of the frigatebird. Subsequently we conducted an educational program about frigatebirds by means of penyuluhan, an Indonesian style, culturally-sensitive, informal discussion technique. There was significantly greater positive perception of Frigatebirds in the group attending a series of informative penyuluhan meetings compared to the control group. As Indonesia has a strong oral tradition, we believe that this method offers potential benefits as a tool to improve conservation outcomes for threatened species.